(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The frequency of childhood blindness and its causes in community-based and blind schools, respectively, from 1990 onwards, were the subject of a thorough search to find research publications from up to the present. To expand the reference data, manual searches of cross references and professional consultation were also conducted. There were discovered to be five community-based research on the prevalence, including two investigations on refractive error in children under the age of 16 that were undertaken throughout India. According to the available blind school research, whole globe anomalies have largely replaced corneal causes as the principal causes of juvenile blindness. This article emphasizes that although the trend is changing due to the availability of adequate healthcare facilities, much work is still needed in the form of timely neonatal eye care facilities, pediatric surgical treatments, and appropriate refractive procedures.